Imaginário poético na obra de Itamar Pires Ribeiro - Oliveira, Juscelino Alves de (2017)
This research divide itself into three parts, is focused on analyzes and reflections on Itamar Pires Ribeiro's lyric, especially in poems from two of his books, “Das Palavras” and “A Arte de Pintar Elefantes”, both published in 2000, with the aim of developing studies on the artist's poetic imagery. We had the specific intention of analyzing the relation of the poet and his creation, the very matter of his production. “As Palavras” ("The Words"), “Água” ("Water"), "Pantera", “Canção do Amor Irônico” ("Song of Ironic Love"), “Paixão” ("Passion") and “Vinho” ("Wine") are among the analyzed poems, exemplifying the arduous poetic exercise, its muses, its images. The main methodology used was the bibliographical research, through the approach of concepts and analyzes on the poetic text, involving Gilbert Durand's theories about the imaginary’s anthropological structures. Other theorists such as Susanne K. Langer and Octavio Paz were also approached in our study, which had its first part a panoramic look at the artistic whole of the poetic work of Ribeiro; In the second part, we analyze the selected poems with the theoretical lens of Durand and others; In the third, we try to show some elements visualized by us in the poetic work of the author. There is also an attached interview with the author, where he talks about his artistic work, the relationship between the lived time and his creation, his muses, his creative methods, and other questions. We hope that this work may contribute to the development of new studies on the poetry of Itamar Pires Ribeiro that show the relevance of this poet's work.